Analisis Efektivitas Pelaksanaan Pendidikan dan Pelatihan Dalam Peningkatan Kinerja SDM di Unit (PPA) Perlindungan Perempuan dan Anak Pada Polres Nias - Dian Permatasari Zebua; Suka'aro Waruwu; Fatolosa Hulu; Odaligoziduhu Halawa (Jurnal Publikasi Manajemen Informatika, 2024)
Educational effectiveness is a measure of the success of an organizational goal. The effectiveness of educational institutions consists of the dimensions of school management and leadership, teachers, education staff and other personnel, students, curriculum, infrastructure, classroom management. Training is a place for employees to learn attitudes, skills and skills related to work (Maryadi, 2019 ). In science, there is the aim of this research, the effectiveness of the implementation of education and training in improving human resource performance in the PPA (Women and Child Protection) Unit at Nias Police, the obstacles or challenges faced in implementing education and training programs to improve human resource performance in The Nias Police PPA Unit in protecting women and children from violence, a supporting factor in efforts to increase the number of personnel participating in Education and Training programs, especially handling cases in the PPA Unit. This research uses a qualitative type of research and the object of the research is carried out on natural objects. The data collection techniques used in this research are observation, documentation and interviews. Researchers carry out observations by going directly into the field to see the objects being studied, then conducting interviews with informants to dig up information about the objects being studied and collecting documents. The conclusion of the researcher's objective is the effectiveness of the implementation of education and training in improving the performance of human resources in the PPA (women and child protection) unit at the Nias Police. It has been implemented but there are still human resources working and not yet fully able to implement it.